Bovine mortality causes in the Izeli sector of the Mushie ranch in Democratic Republic of Congo - Edouard Telamanu BAFWANGA; Anicet Ilaka NZASHILUMENGU; Arthur NGULU-NSASI (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2019)
A study was conducted in 2014 on N’dama cattle in the Izeli sector of the Mushie ranch in DR Congo. The objectives were: (1) to identify the different causes of mortality of pathological and non-pathological origin, (2) to determine the number of cases, the frequency and the mortality rate for each cause according to whether calves, adult cattle (including cows) and cows apart. The methodology consisted of taking into account all verified mortality cases recorded during the year. The causes of death were identified through a few techniques including buffy coat, PCR, clinical examinations, autopsy reports, post mortem examinations and the use of documentary technique (annual report of the ranch). The Excel software was used for data entry while the SPSS 21 for their processing. The% allowed to determine the frequency and the mortality rate for each cause. The results revealed 23 causes of death that resulted in the death of 283 cattle, of which 45.99% (n = 129) were of pathological origin and 54.41% (n = 154) non-pathological.